Factors Influencing Stunting Incidence - Nurlela Mariana Nababan (International Journal Of Health Science, 2023)
Stunting conditions due to chronic malnutrition and nutritional deficiencies that caused the child to fail to grow according to his age, Stunting prevalence is 21.6% of the number of newborns in Indonesia, and the number of stunting sufferers is increasing due to several factors, one of which is the economy, so that families ignore the nutritional needs of the newborn. The method used in this study is simple random sampling. The number of samples used as respondents was 112 households. There are several factors that influence stunting: the mother’s knowledge of exclusive breastfeeding, sanitation of the environment, antenatal care, and visits of health officials based on statistical tests. There is a significant relationship where the p-value value is 0.015 = 0.07; this proves to be a relationship for every factor causing stunting. The conclusion and recommendation of increased stunting incidence are indicators of inequality in health care, so it is expected that health workers should improve nutritional status.